Robust Unit Commitment for Minimizing Wind Spillage and Load Shedding With Optimal DPFC - Zhu, Xuedong; Wu, Jun; Liu, Dichen (Frontiers in Energy Research, 2022)
Distributed Power Flow Controller has a positive effect of UC problem on network side based on its manage capacity of power flow. This study presents a novel two-stage robust model to optimize the status of generator and location-allocation of DPFC simultaneously considering wind and load uncertainties. The Column and constraint generation(CCG) method is utilized to solve the two-stage problem into the master problem and the subproblem iteratively. The optimal status of generator and location of DPFC can be easily obtained with the master problem, the dispatch solution and compensation level of DPFC are solved in the subproblem. We conduct the IEEE 24 bus system to verify the performance of the proposed procedure. There are effects on Wind spillage/load shedding and generator dispatch scheduling planning once DPFC injected. Detailed simulation results illustrate the effect of the proposed approach.